Crystallization precipitation type self-healing agent for well cementation as well as preparation method and application of crystallization precipitation type self-healing agent

By encapsulating the crystal precipitation self-healing agent coated with sodium silicate, the seal failure problem caused by micro-cracks of cement cement stone is solved, and rapid self-healing and long-term effects are achieved without affecting the performance of the cement slurry.

CN119874249AActive Publication Date: 2025-04-25CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510155763.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-25
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

The existing cement cement stone is prone to micro-cracks under stress and strain, resulting in cementing seal failure. The existing self-healing technology responds slowly or is difficult to repair large cracks. The direct addition of sodium silicate will affect the safety of pump injection.

Method used

By using a crystalline precipitate self-healing agent encapsulated with sodium silicate, by providing a potential calcium source, when cementite is damaged by stress, the coated sodium silicate is released and reacts with the calcium source, quickly forming calcium silicate enrichment and blocking microcracks.

Benefits of technology

The self-healing process is accelerated, the self-healing speed and action time are improved, and there is basically no impact on the performance of cement slurry.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of oil and gas well cementation, and particularly relates to a crystal precipitation type self-healing agent for well cementation and a preparation method and application thereof. The crystallization precipitation type self-healing agent for well cementation comprises the following raw materials: 1-7 parts of sodium silicate, 1-4 parts of a balling material, 4-6 parts of resin, 0.2-0.5 part of a saturated sodium silicate solution and 0.5-1.5 parts of a dispersing agent. The self-healing agent is prepared by packaging and coating sodium silicate, a potential calcium source is provided in the coating process, when set cement is damaged due to stress, the coated sodium silicate is released and reacts with the calcium source, calcium silicate enrichment is rapidly formed in set cement microcracks, and the self-healing process is accelerated. The self-healing agent disclosed by the invention is high in self-healing speed, long in acting time and simple in preparation process, and basically has no influence on the performance of cement paste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil and gas cementing, and in particular relates to a crystal precipitation type self-healing agent for cementing, and a preparation method and application thereof. Background Art

[0002] Cementing stone is a hard and brittle material. Due to various stresses and strains during underground service, it is difficult to avoid micro cracks. When micro cracks appear in cement stone, cementing seal failure will occur. The most direct solution is to squeeze cement or squeeze resin to seal, but the squeezing operation is risky and costly.

[0003] The self-healing technology of cement paste micro-cracks is an effective way to solve cementing failure. At present, there are three main self-healing mechanisms: expansion and clogging of pores by formation water or hydrocarbons; crystal precipitation and clogging of pores; microcapsules release solidifying materials. Among them, fiber microcapsules are not suitable for high shear conditions of cementing pumping. The advantage of expansion and clogging of pores by formation water or hydrocarbons is rapid reaction, but the material durability is poor in the well. The advantage of crystal precipitation and clogging of pores is good material durability, but the reaction is slow, it takes dozens of days to achieve healing, and it is difficult to repair large cracks.

[0004] Sodium silicate can react with calcium ions in cement slurry to form calcium silicate gel precipitation. The reaction process is fast, and the formed calcium silicate has adhesion properties. If sodium silicate can be used in cement slurry as a crystal precipitation type self-healing agent, it will effectively solve the sealing failure problem caused by micro cracks in cement stone. However, adding sodium silicate directly to cement slurry will cause the cement slurry to solidify quickly, seriously affecting pumping safety. Summary of the invention

[0005] In view of the problems in the prior art, the present invention provides a crystalline precipitation type self-healing agent for cementing and a preparation method thereof, and applies the same to cementing of oil and gas wells. The self-healing agent is prepared by encapsulating and coating sodium silicate, providing a potential calcium source during the coating process. When the cement stone is damaged by stress, the coated sodium silicate is released and reacts with the calcium source to form calcium silicate enrichment in the microcracks of the cement stone more quickly. Compared with conventional crystalline precipitation type self-healing agents, the self-healing process is accelerated and the action time is long.

[0006] The crystal precipitation self-healing agent for cementing of the present invention comprises the following raw materials: 1-7 parts of sodium silicate, 1-4 parts of spherical material, 4-6 parts of resin, 0.2-0.5 parts of saturated sodium silicate solution and 0.5-1.5 parts of dispersant.

[0007] The ball-forming material is a mixture of metakaolin and slag, the ratio of metakaolin to slag is 1:1-2:1, and the particle size is 300-2000 mesh.

[0008] The resin is a mixture of phenolic resin and epoxy resin, and the mass ratio of phenolic resin to epoxy resin is 3:1-5:1.

[0009] The dispersant is calcium hydroxide powder or calcium sulfate powder with a particle size of 800-2000 meshes.

[0010] The preparation method of the crystal precipitation type self-healing agent for cementing comprises the following specific steps: (1) Pour sodium silicate and spherical materials into a disc granulator, and spray saturated sodium silicate solution while rotating the disc granulator to obtain particles I; spraying the sodium silicate solution can bond the spherical materials to the surface of the sodium silicate particles. At the same time, the saturated sodium silicate solution can prevent the sodium silicate particles from being dissolved.

[0011] (2) Calcinate particle I to obtain particle II. After calcination, particle I will have a certain strength, which is convenient for subsequent coating of resin on its surface. Otherwise, particle II will break when subjected to external force. The calcination temperature is 600℃-900℃.

[0012] (3) Prepare a mixed system of phenolic resin and epoxy resin, mix particles II and the resin mixed system evenly, add a dispersant, disperse the resin-coated particles II, and obtain particles III; the mass ratio of particles II to the resin mixed system is 10:3~2:1.

[0013] (4) Particle III is heated and cured to form a crystalline precipitation type self-healing agent. The resin curing time at room temperature is as long as 24 hours, and the cross-linking degree of the resin cured at room temperature is not high, which leads to poor packaging effect. After heating and curing, the resin curing time can be shortened to 1 hour, and the cross-linking degree of the heated cured resin is high. The curing temperature is 85-95℃.

[0014] The present invention uses metakaolin and slag, which have the following effects: (1) can ensure that sodium silicate is well dispersed; (2) can protect the sodium silicate particles, achieve the slow release of sodium silicate to a certain extent, and ensure that the self-healing agent has a certain strength.

[0015] The present invention adopts phenolic resin and epoxy resin compounding, and the amount of phenolic resin is mainly used, mainly to utilize the brittleness of phenolic resin after solidification, when cement stone is damaged by stress, the phenolic resin coating layer can be damaged, and sodium silicate is released. The effect of adding epoxy resin is to increase the viscosity of phenolic resin, which can better adhere to the surface of microsphere particles. The resin forms a continuous protective film on the surface of microsphere, and acts together with the coating layer formed by metakaolin and slag, further enhancing the protection of sodium silicate, ensuring that before microcracks are generated in the slurry preparation and cement stone curing process, sodium silicate will not be released. At the same time, it is ensured that after the cement stone produces microcracks, a channel is provided for the timely release of sodium silicate.

[0016] In the present invention, calcium hydroxide and calcium sulfate provide calcium sources for sodium silicate reaction, accelerate the formation of calcium silicate, and improve the healing speed.

[0017] In the self-healing process of cementing, different stages require different amounts and speeds of sodium silicate release. At the initial stage of the crack, a certain amount of sodium silicate needs to be released quickly as soon as the crack appears to initially fill the crack, and then it needs to be released slowly to continue the healing reaction and enhance the healing effect. In the early stage of the crack formation of the self-healing agent described in the present invention, the stress generated by the crack is transmitted to the resin coating layer, so that the resin coating produces microcracks, providing a channel for the release of sodium silicate; after the microcracks in the cement stone are generated, the high humidity environment at the crack will quickly promote the dissolution and diffusion of sodium silicate. In the early stage, the concentration gradient of sodium silicate is large, that is, the concentration of sodium silicate inside the self-healing agent is much higher than the concentration in the microcracks. This large concentration difference will prompt sodium silicate to diffuse rapidly into the microcracks. Subsequently, when cement reacts with sodium silicate, a gelling substance is generated, which is coated on the surface of the microspheres, reducing the contact between the microspheres and the external environment, so that the subsequent release rate of sodium silicate gradually decreases, and a continuous slow release is achieved; and as the sodium silicate is continuously released, the concentration of sodium silicate inside the microspheres gradually decreases, and the concentration difference with the microcracks gradually decreases, and the diffusion rate decreases, so the release rate of sodium silicate gradually slows down, showing a state of continuous slow release. Therefore, compared with the healing time of dozens of days of conventional crystal precipitation type self-healing agents, the self-healing agent of the present invention has a self-healing effect in a shorter time and a longer action time.

[0018] The crystal precipitation self-healing agent for cementing described in the present invention can be used in cementing of oil and gas wells. After the self-healing agent described in the present invention is added to cement slurry, the cement slurry has substantially no change in the compressive strength of the cement stone after thickening time at 90°C and curing at 90°C for 24 hours.

[0019] Compared with the prior art, the present invention has the following beneficial effects: the self-healing agent of the present invention has a fast self-healing speed, a long action time, a simple preparation process and basically no effect on the performance of cement slurry. DETAILED DESCRIPTION

[0020] The cement slurry preparation method is carried out in accordance with "GB / T 19139-2012 Oil Well Cement Test Method". G-grade oil well cement is used, the water-cement ratio is 0.44, the self-healing agent dosage is 5% (cement mass), and the fluid loss reducer (model G33S) dosage is 1.5% (cement mass). In order to study the self-healing effect, the permeability recovery of cement paste is evaluated. After curing in a water bath at 80℃ for 3 days, alternating damage is performed, and the permeability is tested. Then, the permeability is tested again after continuing to cure in a water bath at 80℃ for a certain period of time. If the cement paste self-heals, the permeability of the cement paste is restored. The permeability test is carried out using a pressure-covered porosity test system.

[0021] Comparative Example 1 As an active material, fly ash has a slower hydration rate than cement. When microcracks appear in cement paste, secondary hydration will occur to heal the microcracks in cement paste. Therefore, fly ash is selected for crystallization precipitation self-healing comparison. G-grade oil well cement has a water-solid ratio of 0.44, a fly ash content of 30% (cement mass), and a fluid loss reducer (model G33S) content of 1.5% (cement mass).

[0022] Comparative Example 2 A crystal precipitation type self-healing agent for cementing, the raw material composition of which is: 7 parts of sodium silicate, 3 parts of ball-forming material, and 0.3 parts of saturated sodium silicate solution.

[0023] The ball-forming material is a mixture of metakaolin and slag, the ratio of metakaolin to slag is 2:1, and the particle size is 2000 meshes.

[0024] The specific preparation steps are: (1) Pour a mixture of sodium silicate, metakaolin and slag into a disc granulator, start the machine, and use a disc granulation method to spray a saturated sodium silicate solution while rotating the granulator to form microsphere particles containing sodium silicate, which are recorded as particles I.

[0025] (2) Particle I was calcined at 900°C. The calcined particles were recorded as particles II, forming a crystalline precipitation type self-healing agent S1. The corresponding cement slurry was C1, and the setting time of the cement slurry was significantly shortened. The thickening time of the 90°C cement slurry was shortened to 42 minutes.

[0026] Comparative Example 3 A crystal precipitation type self-healing agent for cementing, the raw material composition of which is: 7 parts of sodium silicate, 3 parts of spherical material, 4 parts of resin, 0.3 parts of saturated sodium silicate solution, and 0.5 parts of dispersant, wherein the dispersant is silica sand powder.

[0027] The ball-forming material is a mixture of metakaolin and slag; the ratio of metakaolin to slag is 2:1, and the particle size is 2000 meshes.

[0028] The resin is a mixture of phenolic resin and epoxy resin, and the mass ratio of phenolic resin to epoxy resin is 3:1.

[0029] The specific preparation steps are: (1) Pour a mixture of sodium silicate, metakaolin and slag into a disc granulator, start the machine, and use a disc granulation method to spray a saturated sodium silicate solution while rotating the granulator to form microsphere particles containing sodium silicate, which are recorded as particles I.

[0030] (2) Calcinate particle I at a temperature of 900°C. The calcined particles are designated as particle II.

[0031] (3) Prepare a phenolic resin and epoxy resin mixed system, and mix the particles II and the resin mixed system evenly. Use silica sand powder with a particle size of 2000 mesh as a dispersant to disperse the resin-coated particles II to form particles III.

[0032] (4) Particle III is heated to 95°C for curing to form a crystalline precipitation type self-healing agent S2, and its corresponding cement slurry is C2.

[0033] Comparative Example 4 A crystal precipitation type self-healing agent for cementing, the raw material composition of which is: 7 parts of sodium silicate, 3 parts of spherical material, 4 parts of resin, 0.3 parts of saturated sodium silicate solution, and 0.5 parts of dispersant, wherein the dispersant is silica sand powder.

[0034] The ball-forming material is slag, and its particle size is 2000 meshes.

[0035] The resin is a mixture of phenolic resin and epoxy resin, and the mass ratio of phenolic resin to epoxy resin is 3:1.

[0036] The specific preparation steps are: (1) Pour a mixture of sodium silicate, metakaolin and slag into a disc granulator, start the machine, and use a disc granulation method to spray a saturated sodium silicate solution while rotating the granulator to form microsphere particles containing sodium silicate, which are recorded as particles I.

[0037] (2) Calcinate particle I at a temperature of 900°C. The calcined particles are designated as particle II.

[0038] (3) Prepare a phenolic resin and epoxy resin mixed system, and mix the particles II and the resin mixed system evenly. Use silica sand powder with a particle size of 2000 mesh as a dispersant to disperse the resin-coated particles II to form particles III.

[0039] (4) Particle III is heated to 95°C for curing to form a crystalline precipitation type self-healing agent S3, and its corresponding cement slurry is C3.

[0040] Comparative Example 5 A crystal precipitation type self-healing agent for cementing, the raw material composition of which is: 7 parts of sodium silicate, 3 parts of spherical material, 4 parts of resin, 0.3 parts of saturated sodium silicate solution, and 0.5 parts of dispersant, wherein the dispersant is silica sand powder.

[0041] The ball-forming material is metakaolin with a particle size of 2000 meshes.

[0042] The resin is a mixture of phenolic resin and epoxy resin, and the mass ratio of phenolic resin to epoxy resin is 3:1.

[0043] The specific preparation steps are: (1) Pour a mixture of sodium silicate, metakaolin and slag into a disc granulator, start the machine, and use a disc granulation method to spray a saturated sodium silicate solution while rotating the granulator to form microsphere particles containing sodium silicate, which are recorded as particles I.

[0044] (2) Calcinate particle I at a temperature of 900°C. The calcined particles are designated as particle II.

[0045] (3) Prepare a phenolic resin and epoxy resin mixed system, and mix the particles II and the resin mixed system evenly. Use silica sand powder with a particle size of 2000 mesh as a dispersant to disperse the resin-coated particles II to form particles III.

[0046] (4) Particle III is heated to 95°C for curing to form a crystalline precipitation type self-healing agent S4, and its corresponding cement slurry is C4.

[0047] Comparative Example 6 A crystal precipitation type self-healing agent for cementing, the raw material composition of which is: 7 parts of sodium silicate, 3 parts of spherical material, 4 parts of resin, 0.3 parts of saturated sodium silicate solution, and 0.5 parts of dispersant, wherein the dispersant is silica sand powder.

[0048] The ball-forming material is a mixture of metakaolin and slag; the ratio of metakaolin to slag is 2:1, and the particle size is 2000 meshes.

[0049] The resin is epoxy resin.

[0050] The specific preparation steps are: (1) Pour a mixture of sodium silicate, metakaolin and slag into a disc granulator, start the machine, and use a disc granulation method to spray a saturated sodium silicate solution while rotating the granulator to form microsphere particles containing sodium silicate, which are recorded as particles I.

[0051] (2) Calcinate particle I at a temperature of 900°C. The calcined particles are designated as particle II.

[0052] (3) Prepare a phenolic resin and epoxy resin mixed system, and mix the particles II and the resin mixed system evenly. Use silica sand powder with a particle size of 2000 mesh as a dispersant to disperse the resin-coated particles II to form particles III.

[0053] (4) Particle III is heated to 95°C for curing to form a crystalline precipitation type self-healing agent S5, and its corresponding cement slurry is C5.

[0054] Example 1 A crystal precipitation type self-healing agent for cementing, the raw material composition of which is: 1 part of sodium silicate, 3 parts of spherical material, 4 parts of resin, 0.3 parts of saturated sodium silicate solution, and 0.5 parts of dispersant.

[0055] The ball-forming material is a mixture of metakaolin and slag; the ratio of metakaolin to slag is 2:1, and the particle size is 300 meshes.

[0056] The resin is a mixture of phenolic resin and epoxy resin, and the mass ratio of phenolic resin to epoxy resin is 3:1.

[0057] The specific preparation steps are: (1) Pour a mixture of sodium silicate, metakaolin and slag into a disc granulator, start the machine, and use a disc granulation method to spray a saturated sodium silicate solution while rotating the granulator to form microsphere particles containing sodium silicate, which are recorded as particles I.

[0058] (2) Calcinate particle I at a temperature of 600°C. The calcined particles are designated as particle II.

[0059] (3) Prepare a mixed system of phenolic resin and epoxy resin, and mix particles II and the resin mixed system evenly. Then use calcium hydroxide powder with a particle size of 800 mesh as a dispersant to disperse the resin-coated particles II to form particles III.

[0060] (4) Particle III is heated to 85°C for curing to form a crystalline precipitation type self-healing agent S6, and its corresponding cement slurry is C6.

[0061] Example 2 A crystal precipitation type self-healing agent for cementing, the raw material composition of which is: 1 part of sodium silicate, 1 part of spherical material, 5 parts of resin, 0.3 parts of saturated sodium silicate solution, and 0.5 parts of dispersant.

[0062] The ball-forming material is a mixture of metakaolin and slag, the ratio of metakaolin to slag is 2:1, and the particle size is 1000 meshes.

[0063] The resin is a mixture of phenolic resin and epoxy resin, and the mass ratio of phenolic resin to epoxy resin is 4:1.

[0064] The specific preparation steps are: (1) Pour a mixture of sodium silicate, metakaolin and slag into a disc granulator, start the machine, and use a disc granulation method to spray a saturated sodium silicate solution while rotating the granulator to form microsphere particles containing sodium silicate, which are recorded as particles I.

[0065] (2) Calcinate particle I at a temperature of 700°C. The calcined particles are designated as particle II.

[0066] (3) Prepare a mixed system of phenolic resin and epoxy resin, and mix particles II and the resin mixed system evenly. Then use calcium hydroxide powder with a particle size of 1500 mesh as a dispersant to disperse the resin-coated particles II to form particles III.

[0067] (4) Particle III is heated to 90°C for curing to form a crystalline precipitation type self-healing agent S7, and its corresponding cement slurry is C7.

[0068] Example 3 A crystal precipitation type self-healing agent for cementing, the raw material composition of which is: 2 parts of sodium silicate, 1 part of spherical material, 6 parts of resin, 0.3 parts of saturated sodium silicate solution, and 0.5 parts of dispersant.

[0069] The ball-forming material is a mixture of metakaolin and slag; the ratio of metakaolin to slag is 2:1, and the particle size is 1500 meshes.

[0070] The resin is a mixture of phenolic resin and epoxy resin, and the mass ratio of phenolic resin to epoxy resin is 5:1.

[0071] The specific preparation steps are: (1) Pour a mixture of sodium silicate, metakaolin and slag into a disc granulator, start the machine, and use a disc granulation method to spray a saturated sodium silicate solution while rotating the granulator to form microsphere particles containing sodium silicate, which are recorded as particles I.

[0072] (2) Calcinate particle I at a temperature of 800°C. The calcined particles are designated as particle II.

[0073] (3) Prepare a phenolic resin and epoxy resin mixed system, and mix the particles II and the resin mixed system evenly. Then use ultrafine calcium sulfate powder with a particle size of 1250 mesh as a dispersant to disperse the resin-coated particles II to form particles III.

[0074] (4) Particle III is heated to 95°C for curing to form a crystalline precipitation type self-healing agent S8, and its corresponding cement slurry is C8.

[0075] Example 4 A crystal precipitation type self-healing agent for cementing, the raw material composition of which is: 7 parts of sodium silicate, 4 parts of spherical material, 5 parts of resin, 0.2 parts of saturated sodium silicate solution, and 1.5 parts of dispersant.

[0076] The ball-forming material is a mixture of metakaolin and slag; the ratio of metakaolin to slag is 1:1, and the particle size is 2000 meshes.

[0077] The resin is a mixture of phenolic resin and epoxy resin, and the mass ratio of phenolic resin to epoxy resin is 5:1.

[0078] The specific preparation steps are: (1) Pour a mixture of sodium silicate, metakaolin and slag into a disc granulator, start the machine, and use a disc granulation method to spray a saturated sodium silicate solution while rotating the granulator to form microsphere particles containing sodium silicate, which are recorded as particles I.

[0079] (2) Calcinate particle I at a temperature of 900°C. The calcined particles are designated as particle II.

[0080] (3) Prepare a phenolic resin and epoxy resin mixed system, and mix the particles II and the resin mixed system evenly. Then use ultrafine calcium sulfate powder with a particle size of 1000 mesh as a dispersant to disperse the resin-coated particles II to form particles III.

[0081] (4) Particle III is heated to 90°C for curing to form a crystalline precipitation type self-healing agent S9, and its corresponding cement slurry is C9.

[0082] Table 1 Cement stone permeability recovery test .

[0083] The self-healing agent of the present invention can achieve self-healing of cement paste microcracks within 14 days, and the self-healing effect is enhanced after 28 days, and the self-healing effect is still exerted, and has the advantages of fast action speed, long action time, simple preparation process, and basically no effect on cement slurry performance.

Claims

1. A crystal precipitation type self-healing agent for cementing, characterized in that: The raw material composition is: 1-7 parts of sodium silicate, 1-4 parts of spherical material, 4-6 parts of resin, 0.2-0.5 parts of saturated sodium silicate solution and 0.5-1.5 parts of dispersant.

2. A crystalline precipitation type self-healing agent for cementing according to claim 1, characterized in that: The ball-forming material is a mixture of metakaolin and slag; in terms of mass ratio, the metakaolin:slag = 1:1-2:1; and the particle size is 300-2000 meshes.

3. A crystalline precipitation type self-healing agent for cementing according to claim 1, characterized in that: The resin is a mixture of phenolic resin and epoxy resin, and the mass ratio of phenolic resin to epoxy resin is 3:1-5:

1.

4. A crystalline precipitation type self-healing agent for cementing according to claim 1, characterized in that: The dispersant is calcium hydroxide powder or calcium sulfate powder.

5. The method for preparing the crystalline precipitation type self-healing agent for cementing according to any one of claims 1 to 4, characterized in that: The specific steps are: (1) Pour sodium silicate and spherical materials into a disc granulator, and spray a saturated sodium silicate solution while rotating the disc granulator to obtain granules I; (2) calcining particle II to obtain particle II; (3) preparing a mixed system of phenolic resin and epoxy resin, mixing particles II and the mixed resin system evenly, adding a dispersant, dispersing the particles II coated with the resin, and obtaining particles III; (4) Particle III is heated and cured to form a crystalline precipitation type self-healing agent.

6. The method for preparing the crystal precipitation type self-healing agent for cementing according to claim 5, characterized in that: The calcination temperature in step (2) is 600°C-900°C.

7. The method for preparing the crystal precipitation type self-healing agent for cementing according to claim 5, characterized in that: The curing temperature in step (4) is 85-95°C.

8. Use of the crystalline precipitation self-healing agent for cementing according to any one of claims 1 to 4 in cementing of oil and gas wells.

Citation Information

Patent Citations

  • Concrete waterproof agent

    CN108191296A

  • Oil well micro-crack self-healing material and preparation method thereof

    CN111072328A

  • Deep permeable crystallization self-healing waterproof material as well as preparation method and application thereof

    CN118206340A

  • Microcapsule modified ash geopolymer self-healing separating wall material and preparation process thereof

    CN118771769A

  • Engineered self-healing hydraulic-cement concrete by biomimicry

    WO2024191431A1